2020
DOI: 10.1002/micr.30677
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative vasopressors in head and neck free flap reconstruction

Abstract: Introduction Historically, there were concerns vasopressors impair free flap outcomes, but recent studies suggest vasopressors are safe. Here we investigate this controversy by (1) evaluating vasopressors' effect on head and neck free‐flap survival and surgical complications, and (2) performing soft tissue and bony subset analysis. Patients and methods Post hoc analysis was performed of a single‐blinded, prospective, randomized clinical trial at a tertiary care academic medical center involving patients ≥18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The overall free flap survival rate was 75/79 (95%). Investigators found no significant difference in flap failure or flap‐related complications between the vasopressor group and the traditional protocol group 23 . A fourth RCT with an intention‐to‐treat analysis randomized 27 patients into one of three unblinded groups, in which patients would either be controls (given fluids if MAP <60 mm Hg), or receive dopamine (maximum dose 13.3 mcg/kg/min) or norepinephrine to maintain MAP 80–90 mm Hg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall free flap survival rate was 75/79 (95%). Investigators found no significant difference in flap failure or flap‐related complications between the vasopressor group and the traditional protocol group 23 . A fourth RCT with an intention‐to‐treat analysis randomized 27 patients into one of three unblinded groups, in which patients would either be controls (given fluids if MAP <60 mm Hg), or receive dopamine (maximum dose 13.3 mcg/kg/min) or norepinephrine to maintain MAP 80–90 mm Hg.…”
Section: Resultsmentioning
confidence: 99%
“…Investigators found no significant difference in flap failure or flap-related complications between the vasopressor group and the traditional protocol group. 23 A fourth RCT with an intention-to-treat analysis randomized 27 patients into one of three unblinded groups, in which patients would either be controls (given fluids if MAP <60 mm Hg), or receive dopamine (maximum dose 13.3 mcg/kg/min) or norepinephrine to maintain MAP 80-90 mm Hg. Patients were monitored postsurgery for 72 h with continuous measurement of tissue partial pressure of oxygen and microdialysis metabolite measurements.…”
Section: Prospective Studiesmentioning
confidence: 99%
“…The growing consensus of available data show that vasopressor use intraoperatively does not decrease free flap survival. [19][20][21][22][23] In fact, studies show vasopressors can improve free flap skin paddle blood flow 24 and are preferred to large-volume resuscitation. 25,26 Some of the anastomotic revisions without thrombectomy in the current study may have been performed in response to vasospasm.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, microvascular surgeons were hesitant to use vasopressors, with the belief that the flap pedicle is hypersensitive to vasoconstrictor medications, potentially endangering the flap. The growing consensus of available data show that vasopressor use intraoperatively does not decrease free flap survival 19‐23 . In fact, studies show vasopressors can improve free flap skin paddle blood flow 24 and are preferred to large‐volume resuscitation 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is now a robust and growing body of literature demonstrating efficacy and safety of vasopressor use in microsurgery (Brinkman et al, 2013; Naik et al, 2020; Swanson et al, 2016; Taylor et al, 2021) (Table 1). Several studies demonstrate no differences in the flap failure incidence between flaps exposed to pressor versus not (Fang et al, 2018; Heine‐Geldern et al, 2019; Knackstedt et al, 2019; Naik et al, 2020; Swanson et al, 2016).…”
Section: Safety Of Vasopressor Use In Microsurgery For Perioperative ...mentioning
confidence: 99%